Antioxidative defense response to Aphid-induced oxidative stress in Glycine max (L.) Merr. cv. “Nam Dan” - Toan, Tran Ngoc; Thanh Huyen, Tran Thi; Chung, Mai Van (Vietnam Journal of Science and Technology, 2016)
Infestation of cowpea aphid (Aphis craccivora Koch) induced oxidative stress in leaves of soybean (Glycine max (L.) Merr. cv. “Nam Dan”) with a burst in generation of reactive oxygen species (ROS) products such as superoxide anion radical (O2.-) and hydrogen peroxide (H2O2) recorded around 24 hours after aphid feeding. An increase in content of thiobarbituric acid reactive substances (TBARS) in lipid peroxidation and a defined percentage of injury in aphid-infested leaves were resulted from the cellular oxidative damage. The enhanced activity of the antioxidant enzymes such as superoxide dismutase (SOD, EC 1.15.1.1) and catalase (CAT, EC 1.11.1.6) in leaves of soybean “Nam Dan” functions as the antioxidative response that controlled both ROS-generation to be enough levels to play as defensive element and ROS-detoxifying to reduce aphid-induced oxidative damage. The enhancement of SOD and CAT also can improve the tolerance of soybean “Nam Dan” to impact from A. craccivora.